Work context in the automotive industry and damage to workers health - Bruning, Camila; de Faria, José Henrique; Marques Junior, Karlo (Revista de Administração da UFSM, 2020)
This paper analyzes the relationship between (i) worker’s perception about their working context and (ii) the physical, social and psychological damage that they perceive having from working in this context. Data were collected in the production line of three factories of an automotive company situated in the metropolitan region of Curitiba/Brazil. The theoretical basis for the analysis is the Psychodynamics of Work (DEJOURS, 1993), through which the dynamics of suffering and illness of workers inserted in this context is analyzed. We conducted a descriptive case study with primary data collection by applying the Inventory of Work and Illness Risk – ITRA (MENDES, 2007). The relationship between physical and psychosocial damage and the perception of workers in relation to their work environment were evaluated by a Tobit regression model. The results suggest that: a worsening in the workers rating of the working conditions leads to a higher incidence of illnesses. The results also suggest that variables such as “freedom of expression”, “experiences of pleasure”, “experiences of suffering” and “perception of recognition” are important to explain incidence of disease symptoms.